Adaptive retrieval, composition & presentation of closed-corpus and open-corpus information - Steichen, Ben (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
A key challenge for information access systems lies in their ability to deliver information that is most suited to a user's needs, preferences and context. Personalised Information Retrieval (PIR) seeks to address this challenge by tailoring the selection of results to each individual user. Such PIR systems typically generate adaptive result rankings based on historic user interests or location properties.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.